2013
DOI: 10.1007/978-94-007-6331-9_5
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns(4)P Signalling and Recognition Systems

Abstract: The Golgi apparatus is a sorting platform that exchanges extensively with the endoplasmic reticulum (ER), endosomes (Es) and plasma membrane (PM) compartments. The last compartment of the Golgi, the trans-Golgi Network (TGN) is a large complex of highly deformed membranes from which vesicles depart to their targeted organelles but also are harbored from retrograde pathways. The phosphoinositide (PI) composition of the TGN is marked by an important contingent of phosphatidylinositol-4-phosphate (PtdIns(4)P). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 169 publications
0
8
0
Order By: Relevance
“…It is also important for autophagy, a survival-promoting pathway leading to the lysosomal degradation of organelles [31]. PI(4)P is enriched in the Golgi apparatus, and is thought to be important for membrane trafficking through the Golgi compartments and from the Golgi to the plasma membrane and other subcellular compartments [32], likely including disk membranes. PI(4,5)P 2 plays a key role in clathrin-mediated endocytosis, and serves to direct many effector proteins to the plasma membrane where it is primarily found [33].…”
Section: Importance Of Phosphoinositides For Dynamics and Functions Omentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important for autophagy, a survival-promoting pathway leading to the lysosomal degradation of organelles [31]. PI(4)P is enriched in the Golgi apparatus, and is thought to be important for membrane trafficking through the Golgi compartments and from the Golgi to the plasma membrane and other subcellular compartments [32], likely including disk membranes. PI(4,5)P 2 plays a key role in clathrin-mediated endocytosis, and serves to direct many effector proteins to the plasma membrane where it is primarily found [33].…”
Section: Importance Of Phosphoinositides For Dynamics and Functions Omentioning
confidence: 99%
“…A number of early reports in the 1980s suggested that light had measurable impacts on PI metabolism in photoreceptors or the retina generally. Based on measurement of 32 Pi incorporated into PtdIns by metabolic labeling, it was reported that exposure of isolated frog retina to light decreased levels of PIP 2 by 14% after 5 s and 37% after 15 s, while levels of PI(4)P, PtdIns and other acidic lipids remained essentially constant [76]. Subsequent publications from the same group reported increased levels of 3 H inositol and 32 P into phosphoinositides upon illumination [77].…”
Section: Evidence For Effects Of Light On Phosphoinositide Metabolismmentioning
confidence: 99%
“…Several proteins have been identified that bind to PtdIns(4)P and function at the Golgi. Here we discuss a few of these proteins, and refer to other recent reviews for a more comprehensive list of PtdIns(4)P effectors [17,18]. …”
Section: Ptdins(4)p and Its Effectors At The Golgimentioning
confidence: 99%
“…Conserved basic residues present in the 3-1 region of the PX domain are believed to mediate interaction with the phosphate groups of phosphatidylinositol phosphates (PIPs) within membranes (Cheever et al, 2001;Ellson et al, 2001;Song et al, 2001;Xu et al, 2001). These PIPs are phosphorylated derivatives of phosphatidylinositol that constitute a small fraction of the total cellular lipids but are important components of cellular organization (Lenoir & Overduin, 2013). Phosphorylation at the 3 0 -, 4 0 -and 5 0hydroxyl groups of the inositol ring leads to seven different phosphatidylinositol phosphates.…”
Section: Introductionmentioning
confidence: 99%